Atypical Hemolytic Uremic Syndrome with Eosinophilia and Purtscher-like Retinopathy: A Case Report - MEI Qimin; DAI Jiayuan; LIU Yecheng; SHEN Min; ZHU Huadong (Xiehe Yixue Zazhi)
Atypical hemolytic uremic syndrome (aHUS), a rare disease caused by complement abnormalities, is characterized by microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. In this paper, we report a patient with severe renal insufficiency with rapidly progressive decline in binocular visual acuity, who developed eosinophilia during the course of the disease, and was diagnosed with aHUS after excluding other diseases. After glucocorticoid treatment, eosinophils decreased to normal, and after treatment with plasmapheresis combined with eculizumab, renal function tended to be stable, platelets returned to normal, but visual acuity did not improve significantly. This article reviews the diagnosis and treatment process of this patient and incorporates the review of literature, in the hope of providing reference for clinicians.